The use of Some Aliphatic Halorgano antimony Compounds as combustion Retarding agents of Unsaturated Polyester and Epoxy Resins - Baghdad Science Journal (مجلة بغداد للعلوم)
Four antimony compounds were used in this inves as additives to retard combustion of unsaturated polyester and epoxy resins, namely: 1. Tetraethyl ammonium tribromoethylantimonates (additive I). 2. Tetraethyl ammonium chlorodibromoethylantimonates (additive II). 3. Tetraethyl ammonium trichloroethylantimonates (additive III). 4. Tetraethyl ammonium bromodichloroethylantimonates (additive IV).